Seed Science and Technology Biology, Production, Quality - Dadlani, Malavika; Yadava, Devendra K. (Springer Nature Singapore : Imprint: Springer, 2023)
This open-access edited book is a collection of 17 chapters, synthesized primarily from the lectures delivered by eminent Indian and international experts during a series of capacity-building programmes organised in India during 2020 and 2021 under the aegis of 'Indo-German Cooperation on Seed Sector Development', a component of the Bilateral Cooperation between the Governments of India and Germany. Seed Science and Technology, a multi-disciplinary subject, is advancing rapidly keeping pace with the development of improved plant varieties and other climate-resilient technologies. Knowledge of the underlying biological processes and application of appropriate technologies for variety maintenance and seed production; quality assurance, testing and enhancement; processing, packaging and storage etc., are important in a seed programme. Chapters presented in the book is a blend of basic seed biology covering seed development, maturation, dormancy, germination, vigour and invigoration, and seed deterioration; variety maintenance and production of genetically pure seed of open-pollinated and hybrid varieties in a few key field crops and vegetables, and fundamentals of seed processing, packaging and storage; and seed quality assurance systems followed in different countries; testing the essential components of seed quality including seed health, application of molecular technologies for precision in testing, and enhancement of seed quality. It concludes by identifying the key areas of future seed research and technology development. The book covers the fundamentals and recent advances of seed science and technology with the latest research information and an exhaustive and updated list of references on different topics. It is expected to benefit the students as well as the scientists, faculty members and seed sector professionals, working in the public and private seed sectors, certification authorities and seed producingagencies in India, and elsewhere. .